Central and Regional Financial Balance: Juridical-Theoretical Dimension - I Dewa Gede Atmadja; I Gusti Ngurah Supartha Jelantik (Sociological Jurisprudence Journal, 2018)
The juridical dimension of the constitution determines that the balance of central and regional finance constitutes imperative prescriptions / norms of central and regional relations (Article 18 jo Article 18 A Paragraph (1) and (2) of the 1945 Constitution. The core norm of central and regional financial balances affirms a regulation of funding as a sub-system of state finances in funding governmental affairs under the jurisdiction of decentralization, deconcentration and co-administration (vide Article 279 of Law Number 23 Year 2014 on Regional Government jo Article 2 of Law Number 33 Year 2004 Concerning Financial Balance Between the Central Government and Government Area). The relationship of central and regional authority is theoretically closely related to the doctrine or household teachings, namely the teaching of material autonomy, the teachings of the household/formal autonomy, and the teachings of real autonomy/real. The teachings of real autonomy or real rely on the idea; from the beginning the center to give recognition to the real situation or factor that grows and develops in the local community. A more comprehensive revitalization and reformulation of central and regional fiscal reforms can be made through the legal authorities of upgrading regional initiatives in accordance with the broadest real autonomy principles, implementing constitutional mandates on other resources that have not been transparently regulated in legislation and required a grand design of Indonesia's fiscal decentralization.